Epigenetic Regulation of TET1-SP1 During Spermatogonia Self-Renewal and Proliferation - Liu, Lingling; Wang, Jin; Wang, Shenghua; Wang, Mudi; Chen, Yuanhua; Zheng, Liming (Frontiers in Physiology, 2022)
Spermatogonia are the source of spermatogenic waves. Abnormal spermatogonia can cause ab-normal spermatogenic waves, which manifest as spermatogenic disorders such as oligospermia, hypospermia, and azoospermia. Among them, the self-renewal of spermatogonia serves as the basis for maintaining the process of spermatogenesis, and the closely regulated balance between self-renewal and differentiation of spermatogonia can maintain the continuous production of spermatozoa. Tet methylcytosine dioxygenase 1(TET1) is an important epitope modifying enzyme that catalyzes the conversion of 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC), thereby causing the methylation of specific genes site hydroxylation, enabling the DNA de-methylation process, and regulating gene expression. However, the hydroxymethylation sites at which TET1 acts specifically and the mechanisms of interaction affecting key differential genes are not clear. In the present study, we provide evidence that the expression of PLZF, a marker gene for spermatogonia self-renewal, was significantly elevated in the TET1 overexpression group, while the expression of PCNA, a proliferation-related marker gene, was also elevated at the mRNA level. Significant differential expression of SP1 was found by sequencing. SP1 expression was increased at both mRNA level and protein level after TET1 overexpression, while differential gene DAXX expression was downregulated at protein level, while the expression of its reciprocal protein P53 was upregulated. In conclusion, our results suggest that TET1 overexpression causes changes in the expression of SP1, DAXX and other genes, and that there is a certain antagonistic effect between SP1 and DAXX, which eventually reaches a dynamic balance to maintain the self-renewal state of spermatogonia for sustained sperm production. These findings may contribute to the understanding of male reproductive system disorders.